Quality of life among physicians in Egypy and its influencing factors: a cross-sectional study - Abdelrahman, Amira Ismail; Goda, Nora Atef; Bendary, Mohamed Mahmoud (Intelektual Pustaka Media Utama, 2024)
Doctors have an essential role in healthcare service, and their quality of life (QoL) is crucial for their professional satisfaction and overall well-being. This study assessed the QoL among physicians and explored the influencing factors that affect it. This cross-sectional study was carried out using a self-administered Internet survey. The survey was focused on physicians employed at various hospitals and clinics in Egypt. Data on participants' demographics, work-related factors, and QoL were collected using WHOQOL-BREF. WHOQOL-BREF questionnaire measures a participant's perception of their life quality across various domains, including general health, physical well-being, psychological health, social relationships, and the environment. The scores for each domain are calculated based on participants' responses to specific items, with higher scores indicating a better QoL. The QoL scores were 3.57±1.02 for the general health domain, 12.93±2.49 for physical domain, 12.29±2.67 for psychological domain, 12.87±3.20 for social domain, and 11.00±2.58 for environmental domain. The overall QoL score was 3.64±0.835. The findings indicate a moderate QoL among the participating physicians. The physicians' QoL domains were affected by age, sex, education level, marital status, chronic disease, smoking, speciality, working hours per week, extra working hours, and work experience.